The motive of the symbolic «DEATH» and «RESURRECTION» of the bride in the kazakh betashar wedding ritual: tradition and modernity (Journal of Philosophy Culture and Political Science, 2023)
The ritual of «opening the face» of the bride is practiced by many Turkic people in ethnographic modernity, which is similar even in a purely phonetic name: Kazakh «betashar», Kyrgyz «bet Achar», Tatar «bit Achar» and many others. «Betashar» is translated from Kazakh as «opening the face».Today, this ritual is interpreted by almost all Turkic people as a public presentation of the bride, and for her as a meeting with the family and numerous relatives of the groom. But, its obvious visible function hides a much deeper meaning than it seems at first glance.Conventionally, the betashar ritual can be divided into three interrelated stages: the preparation of the bride’s wedding dress, the rituals held in the father’s house and the very public process of opening the face in the groom’s house. Their characterization, analysis and classification in historical retrospect will reveal not only the peculiarities of the Kazakh ritual «betashar» and its regional differences, but also historical and cultural ties between related peoples.Hence, in the course of the study, retrospective, comparative, structural-functional, and semiotic approaches were used. Their combination will provide a textured manifestation of the semantic construct of the betashar ritual as a common Turkic heritage, the significance of which is only increasing in the era of globalization. The article uses the materials of field research on the modern practice of the betashar ritual collected in different regions of Kazakhstan in 2010-2019.The article was prepared within the framework of the project of the Ministry of Higher Education and Science of the Republic of Kazakhstan AR09259280 «Languages of Kazakh culture as the basis of ethnic identity: semiotics and semantics».Keywords: betashar wedding ritual, tradition, modernity, saukele, motif of symbolic «death» and «resurrection», Kazakhs, parallels and analogies, Turkic heritage.